The Character of the Narrative and the Image of the Narrator in the Short Stories of Robert Benchley and James Thurber - Lola Jalilovna Jalilova, Rajabov Akhtam Uktamovich (International Journal of Advanced Science and Technology, 2020)
The article deals with the literary analysis of thecharacter of the narrative and the image of the narrator in the short stories of American satirists of the beginning of XX century Robert Benchley and James Thurber. The phenomena of intertextuality as one of the most vivid devices implemented by the short story writersis analyzed. The artistic means used by the masters of American satire are diverse. Here we find notorious cartoon, and psychological analysis with a satirical tint, and grotesque, and elements of "wild humor". Writers use hyperbole, satire, and parody to express their negative attitude towards capitalist America. In satirical short stories, all aspects of American life are mercilessly ridiculed: politics, law, religion, journalism, and literature.The article shows thatfor American authors of the twentieth century, the use of comic at the plot, character and sentence levels is most characteristic. A typical feature of American short stories is the construction of the story, where a sharpened plot is necessarily present, leading to a paradoxical, unexpected ending.